Approaches to the classification of sports disciplines, taking into account their influence on the biochemical profile of an athlete - A. V. Zholinsky; Zh. V. Grishina; A. I. Kadykova; G. A. Makarova; R. V. Deev (National Electronic Information Consortium (NEICON), 2022)
There are many classifications of sports disciplines, which base on various approaches, which separately take into account the patterns of training activity, physiology, the risk of collision and injury, etc. In our opinion, it most fully reflects the specifics of sports changes that occur in the body of athletes under the influence of intense physical activity, at the level of biochemical processes. The classification of sports disciplines proposed by us takes into account the influence of the nature of the training process, the specifics of sports loads, the leading type of energy supply of sports work on the biochemical profile of an athlete, which makes it possible to identify the key features that occur in the body of an athlete under the influence of a specific load.